RNA-Seq Analysis Reveals Genes Related to Photoreception, Nutrient Uptake, and Toxicity in a Noxious Red-Tide Raphidophyte Chattonella antiqua - Shikata, Tomoyuki; Takahashi, Fumio; Nishide, Hiroyo; Shigenobu, Shuji; Kamei, Yasuhiro; Sakamoto, Setsuko; Yuasa, Kouki; Nishiyama, Yoshitaka; Yamasaki, Yasuhiro; Uchiyama, Ikuo (Frontiers in Microbiology, 2019)
Aquaculture industries are under threat from noxious red tides, but harm can be mitigated by precautions such as early harvesting and restricting fish feeding to just before the outbreak of a red tide. Therefore, accurate techniques for forecasting red-tide outbreaks are strongly needed. Omics analyses have the potential to expand our understanding of the eco-physiology of these organisms at the molecular level, and to facilitate identification of molecular markers for forecasting their population dynamics and occurrence of damages to fisheries. Red tides of marine raphidophytes, especially Chattonella species, often extensively harm aquaculture industries in regions with a temperate climate around the world. A red tide of Chattonella tends to develop just after an input of nutrients along the coast. Chattonella displays diurnal vertical migration regulated by a weak blue light, so it photosynthesizes in the surface layer during the daytime and takes up nutrients in the bottom layer during the nighttime. Superoxide produced by Chattonella cells is a strong candidate for the cause of its toxicity to bacteria and fishes. Here we conducted mRNA-seq of Chattonella antiqua to identify genes with functions closely related to the dynamics of the noxious red tide, such as photosynthesis, photoreception, nutrient uptake, and superoxide production. The genes related to photosynthetic pigment biosynthesis and nutrient uptake had high similarity with those of model organisms of plants and algae and other red-tide microalgae. We identified orthologous genes of photoreceptors such as aureochrome (five genes), the cryptochrome/photolyase (CRY/PHR) family (6-4PHR, plant CRY or cyclobutane pyrimidine dimer [CPD] Class III, CPD Class II, and CRY-DASH), and phytochrome (four genes), which regulate various physiological processes such as flagellar motion and cell cycle in model organisms. Six orthologous genes of NADPH oxidase, which produces superoxide on the cell membrane, were found and divided into two types: one with several transmembrane domains and another with numerous transmembrane domains. The present study should open the way for analyzing the eco-physiological features of marine raphidophytes at the molecular level.